2010
DOI: 10.1098/rspb.2010.1928
|View full text |Cite
|
Sign up to set email alerts
|

The mixed mating system of the sea palm kelpPostelsia palmaeformis: few costs to selfing

Abstract: Naturally isolated populations have conflicting selection pressures for successful reproduction and inbreeding avoidance. These species with limited seasonal reproductive opportunities may use selfing as a means of reproductive assurance. We quantified the frequency of selfing and the fitness consequences for inbred versus outcrossed progeny of an annual kelp, the sea palm (Postelsia palmaeformis). Using experimentally established populations and microsatellite markers to assess the extent of selfing in progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 57 publications
6
45
0
Order By: Relevance
“…Each replicate was located at the same site at the same general time period and used the same source population in all but the outbred treatments. Although our experiment did not allow us to identify general differences among source populations arising from genetic differentiation (Kusumo et al 2006) from variation in the environmental conditions experienced by each replicate set of plots, our genetic analyses indicated that all source populations were equally represented (Barner et al 2011). Because of the large area required to carry out the experiments, plots were reused to gain additional replication once sufficient plots became available following extinctions to allow installation of a complete set of treatments at a site at the same time.…”
Section: J Timothy Wootton and Catherine A Pfister 2118mentioning
confidence: 99%
See 4 more Smart Citations
“…Each replicate was located at the same site at the same general time period and used the same source population in all but the outbred treatments. Although our experiment did not allow us to identify general differences among source populations arising from genetic differentiation (Kusumo et al 2006) from variation in the environmental conditions experienced by each replicate set of plots, our genetic analyses indicated that all source populations were equally represented (Barner et al 2011). Because of the large area required to carry out the experiments, plots were reused to gain additional replication once sufficient plots became available following extinctions to allow installation of a complete set of treatments at a site at the same time.…”
Section: J Timothy Wootton and Catherine A Pfister 2118mentioning
confidence: 99%
“…The sea palm is ideal for this experimental study because it has relatively insular populations (Dayton 1973, Paine 1988, Kusumo et al 2006, Barner et al 2011) that sometimes go extinct (Paine 1979(Paine , 1988. Furthermore, prior observations of populations on the verge of extinction have frequently detected stunted individuals (R. T. Paine, personal communication), leading us to suspect a priori that genetic factors might contribute significantly to extinction risk.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations